Impact of organizational justice on Job performance in Nepalese Quality Assurance Accredited (QAA) College - Sapkota, Shiba Prasad (Nepalese Journal of Management Research, 2021)
Performance of employees’ directly affect the performance of the organizations. Employees’ performance is a core concept within work and organizational psychology. The leader of organization must provide proper attention on employees’ personal needs and concerns. Justice provides psychological empowerment and create a positive perceptions. This study added value by exploring the direct and combined effects of justice dimensions on employees job performance. This study concludes that there is positive significant relationship between perceived distributive justice, procedural justice, interactional justice and job performance of Nepalese QAA Colleges.